Sleep disturbances, quality of life, and ethnicity: the Sleep Heart Health Study. - Baldwin, Carol M; Ervin, Ann-Margret; Mays, Mary Z; Robbins, John; Shafazand, Shirin; Walsleben, Joyce; Weaver, Terri (J Clin Sleep Med, 2010)
STUDY OBJECTIVES: To compare health-related quality of life (HR-QOL) across subgroups defined by sleep disturbances and ethnicity. METHODS: Men (47%) and women (53%) Sleep Heart Health Study participants age 40 and older (N = 5237) underwent overnight polysomnography and completed self-report questionnaires on symptoms of sleep disturbances. The physical and mental composite scales (PCS and MCS) of the Medical Outcomes Study 36-item short form survey assessed HR-QOL and were compared to sleep data. RESULTS: Participants self-identified as Caucasian/White (n = 4482, 86%), African American/Black (n = 490, 9%), or Hispanic/Mexican American (n = 265, 5%). The prevalence of obstructive sleep apnea (OSA) was 17%, frequent snoring was 34%, difficulty initiating or maintaining sleep (DIMS; insomnia symptoms) was 30%, and excessive daytime sleepiness (EDS) was 25%. African American participants with frequent snoring, insomnia symptoms, or EDS had significantly poorer physical health compared to Caucasians (p < 0.001). Hispanics with frequent snoring, insomnia symptoms, or EDS had significantly poorer mental health than Caucasian participants (p <0.001). Neither PCS nor MCS scores differed significantly across ethnic subgroups for participants with moderate to severe OSA (respiratory disturbance index > 15, 4% desaturation). CONCLUSIONS: Across ethnic/racial subgroups, sleep disturbances are associated with worse physical and better mental HR-QOL than the U.S. norm, but this relationship may be moderated by comorbid health conditions. This study replicates and extends prior research indicating differences among minority and non-minority participants and highlights the need for future studies of sleep disturbances with larger samples of minorities that control for comorbid health conditions.
Keywords: African Americans; Cohort Studies; Ethnic Groups; European Continental Ancestry Group; Female; Health Status; Heart Diseases; Hispanic Americans; Humans; Longitudinal Studies; Male; Mental Health; Middle Aged; Polysomnography; Prevalence; Quality of Life; Sleep Apnea, Obstructive; Sleep Initiation and Maintenance Disorders; Sleep Wake Disorders; Snoring; Surveys and Questionnaires; United States